SOCIALIZATION OF THE USE OF VILLAGE FUNDS IN PROVIDING SERVICES FOR VILLAGE COMMUNITY FACILITIES AND INFRASTRUCTURE - Nur Aliah; Riska Franita; Ahmad Omar Chapakia; Tia Novira Sucipto; Ridho Yoandika (CERED Indonesia Institute, 2023)
The Village Fund policy in Indonesia is a strategic fiscal decentralization instrument designed to strengthen village autonomy, accelerate rural infrastructure development, and improve community welfare. However, effective utilization of Village Funds requires adequate governance capacity, participatory planning, transparency, and accountability at the village level. Desa Klambir V, located in Hamparan Perak District, Deli Serdang Regency, faces several challenges related to limited technical understanding of financial management, suboptimal infrastructure prioritization, insufficient transparency, and the absence of systematic maintenance planning. This Community Service Program aimed to enhance the knowledge and capacity of village officials and community representatives in managing Village Funds, particularly for the provision of public facilities and infrastructure services. The program was implemented using a participatory approach through structured socialization sessions, interactive discussions, and practical simulations on planning, budgeting, reporting, and accountability mechanisms. The results indicate an improvement in participants’ understanding of regulatory frameworks, financial governance principles, and the importance of aligning infrastructure spending with measurable service outcomes. Participants demonstrated increased awareness of transparency practices, participatory development planning, and sustainable infrastructure management. The discussions also identified the need for continuous mentoring to strengthen technical reporting competencies and long-term governance capacity. Overall, the program contributed to reinforcing good village governance practices and promoting responsible Village Fund utilization. Strengthened institutional capacity and active community participation are expected to support sustainable rural infrastructure development and improve public service quality in Desa Klambir V.